2023
DOI: 10.1101/2023.02.19.529072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploiting heterogeneity in coupled, two plasmid systems for dynamic population adaptation

Abstract: In synthetic multi-plasmid systems, it is standard to use only plasmids with orthogonal replication mechanisms to avoid phenotypic heterogeneity and ensure plasmid stability. In nature, however, microbial populations actively exploit heterogeneity to survive in fluctuating environments. Here we show that the intentional use of distinct plasmids with identical origins of replications (oris) can help an engineered bacterial population adapt to its environment. We find that copy number coupling between distinct p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Previous work on plasmid copy number regulation has successfully created small-molecule inducible copy number and mutated copy number variants. , Recently, single strains carrying coupled plasmid systems have been developed which are capable of copy number-mediated differentiation and thereby population adaptation. , The single strain contains two distinct plasmids with shared replication machinery, coupling their copy numbers and generating a new source of heterogeneity. The above work with colE1 plasmids has shown that due to shared replication inhibition, two distinct colE1 constructs will share a total copy number but have a flexible distribution of each plasmid.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work on plasmid copy number regulation has successfully created small-molecule inducible copy number and mutated copy number variants. , Recently, single strains carrying coupled plasmid systems have been developed which are capable of copy number-mediated differentiation and thereby population adaptation. , The single strain contains two distinct plasmids with shared replication machinery, coupling their copy numbers and generating a new source of heterogeneity. The above work with colE1 plasmids has shown that due to shared replication inhibition, two distinct colE1 constructs will share a total copy number but have a flexible distribution of each plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…These results align with the findings of Kumar et al and highlight that selective pressure from a single homogeneous inducer causes rapid lysis of subpopulations carrying high copy number of the induced plasmid and thereby leads to decline of this plasmid in the overall population. 14 A fourth strain with different origins of replication on each plasmid served as a comparison to traditional compatible plasmids. Without plasmid coupling the microfluidic experiments showed Strain 4 was unable to adapt to the environmental cues and large-scale cell death occurred across all cell traps (Figure S4).…”
Section: Modeling Of Copy-number Based Patterning To Model the Spatio...mentioning
confidence: 99%
See 3 more Smart Citations